Application of Service-Learning Model to Shape Learners' Civic Engagement in Junior High School - Mutiara Nurmanita; Ridwan Ridwan (Jurnal Paedagogy, 2023)
This research aims to analyze the application of the service learning model to form student civic engagement, which is motivated by the lack of opportunities for students to become subjects in learning and the lack of student involvement in working together as a team. The method used in the research was qualitative with a descriptive approach. The subjects in the research were class VII students at State Junior High School 2 Airmadidi using data collection techniques, namely observation, interviews, and documentation. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The research results showed that applying the service learning model to form civic engagement can be done through steps. First, students were divided into 4-5 heterogeneous members. At this stage, students made notes which were written and summarized. Second, students found and identified problems faced outside the classroom. Students exchange ideas about solutions that will be presented in solving problems. Third, conveying the results to educators to find solutions to problems. The final step was a group presentation in the question-and-answer process and making conclusions. The conclusion shows that the service-learning model can form civic engagement.